Economic crises and the future of the capitalism - Fuat Sekmen (Akademik İncelemeler Dergisi)
In this study, it has been argued that whether the end of capitalism is reached with the recent financial crises which began in 2007 in the U.S. and it has affected all developed and emerging markets. Fundamental factor which determines this expectation is Marx's prediction about the future of capitalism. According to Marx, capitalism will be collapsed because of crises which are inherent in capitalism. However, markets like people and at times they may get sick. It is not a rational expectation about every person in a bed health will pass out. Thus, inconsistencies in markets do not make a sign that free market system will be end in the near future. From the perspective of Austrian school, since market is a result of human action, uncertainty in a market is inevitable. Today, the concept of capitalism is not thought in the meaning of competitive markets which was adopted by classical economists. All information cannot be known individually, however, classical economists assumed that all individuals have all information in a market. When individuals do not have total information, from the perspective of both producers and consumers, inconsistencies are inevitable. In this study, in what periods economies will have economic crises which are called as disease, whether socialism uses resources efficiently, market failure and what should be a role of government are discussed in detail.